Glucose regulates steady-state levels of PDX1 via the reciprocal actions of GSK3 and AKT kinases - Humphrey, Rohan K. (2010)
The pancreatic beta cell is sensitive to even small changes in PDX1 protein levels; consequently, Pdx1 haploinsufficiency can inhibit beta cell growth and decrease insulin biosynthesis and gene expression, leading to compromised glucose-stimulated insulin secretion. Using metabolic labeling of primary islets and a cultured β cell line, we show that glucose levels modulate PDX1 protein phosphorylation at a novel C-terminal GSK3 consensus that maps to serines 268 and 272. A decrease in glucose levels triggers increased turnover of the PDX1 protein in a GSK3-dependent manner, such that PDX1 phosphomutants are refractory to the destabilizing effect of low glucose. Glucose-stimulated activation of AKT and inhibition of GSK3 decrease PDX1 phosphorylation and delay degradation. Furthermore, direct pharmacologic inhibition of AKT destabilizes, and inhibition of GSK3 increases PDX1 protein stability. These studies define a novel functional role for the PDX1 C terminus in mediating the effects of glucose and demonstrate that glucose modulates PDX1 stability via the AKT-GSK3 axis.